ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KONSUMSI PADA MASYARAKAT DI KOTA DENPASAR - Laila Indra Wahyuni; I Komang Gde Bendesa (E-Jurnal Ekonomi Pembangunan, 2023)
Consumption is an activity that will never be separated from everyday life. Household consumption expenditure has a high average contribution to GRDP. There are many factors that are thought to influence the amount of consumption, such as routine assistance (permanent income), non-routine assistance (transitory income), type of business field/field of work, number of family members, online shops, and non-cash payments (e-money). This article aims to find out what factors influence consumption expenditure for durable goods in households in Denpasar City. The data used is micro data derived from the March 2021 National Socioeconomic Survey (Susenas) for Denpasar City, with a total of 878 households in the observation unit. The method used in this study is probit regression analysis with the help of the STATA software analysis tool version 14.0. The results of this study state that the number of family members, online shops, and non-cash payments (e-money) have a positive and significant effect on consumption expenditure for durable goods. Meanwhile, routine assistance, non-routine assistance, and types of business fields/work fields do not have a significant effect on consumption expenditure for durable goods for households in Denpasar City.